Therapeutic role of curcumin and its novel formulations in gynecological cancers - Mohammad Hossein Pourhanifeh; Maryam Darvish; Javad Tabatabaeian; Mahboobeh Rabbani Fard; Reza Mottaghi; Mohammad Javad Azadchehr; Moghaddaseh Jahanshahi; Amirhossein Sahebkar; Hamed Mirzaei (BMC, 2020)
Abstract Gynecological cancers are among the leading causes of cancer-associated mortality worldwide. While the number of cases are rising, current therapeutic approaches are not efficient enough. There are considerable side-effects as well as treatment resistant types. In addition, which all make the treatment complicated for afflicted cases. Therefore, in order to improve efficacy of the treatment process and patients' quality of life, searching for novel adjuvant treatments is highly warranted. Curcumin, a promising natural compound, is endowed with numerous therapeutic potentials including significant anticancer effects. Recently, various investigations have demonstrated the anticancer effects of curcumin and its novel analogues on gynecological cancers. Moreover, novel formulations of curcumin have resulted in further propitious effects. This review discusses these studies and highlights the possible underlying mechanisms of the observed effects.